Protective role of intracellular glutathione against oxidized low density lipoprotein in cultured endothelial cells - Kuzuya, Masafumi; Naito, Michitaka; Funaki, Chiaki; Hayashi, Toshio; Asai, Kanichi; Kuzuya, Fumio (Biochemical and Biophysical Research Communications, 1989)
We examined the role of intracellular glutathione (GSH) in the defense of endothelial cells against oxidized low density lipoprotein (OX-LDL). Incubation of cultured bovine endothelial cells with OX-LDL produced a loss of intracellular GSH, followed by lysis. A decrease in the cellular stores of GSH by treating the endothelial cells with buthionine sulfoximine, an irreversible inhibitor of gamma-glutamylcysteine synthetase, increased the susceptibility of endothelial cells to lysis by OX-LDL. In contrast, an increase in cellular GSH level by treatment with L-2-oxothiazolidine-4-caboxylate, an effective intracellular cysteine delivery agent, reduced the toxicity of OX-LDL. These findings suggest that intracellular GSH plays an important role in the defense of endothelial cells against OX-LDL, and that the mechanism of OX-LDL toxicity is related to the depletion of intracellular GSH.